Trendi intenzivnih padavin v Sloveniji v obdobju 1961-2020 - Mužina, Gašper (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2024)
The spatial distribution of intense precipitation in Slovenia for the period 1961–2020 is consistent with the distribution of mean annual precipitation. Intense precipitation occurs most frequently in the area of the Alpine-Dinaric barrier, which is the wettest part of Slovenia. The number of days with intense precipitation above 30 and 50 mm has generally increased during this period, while it has decreased above 70 mm. An analysis of the trends at the individual stations representing the climate and precipitation conditions in the individual areas showed that in places with a moderate Mediterranean precipitation regime, the peaks of intense precipitation occur more frequently in the autumn, while in areas with a moderate continental precipitation regime they occur more frequently in the summer.
Keywords: climate changes; climatogeography; klimatogeografija; padavine; podnebne spremembe; precipitation; precipitation variability; Slovenia; Slovenija